2020
DOI: 10.4085/1062-6050-264-19
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Slowing on the King-Devick Test and Longer Recovery From Sport-Related Concussion in Adolescents: A Validation Study

Abstract: Context The King-Devick (KD) test is a rapid number-reading test that has emerging use in the assessment of sport-related concussion (SRC). Previous research suggested that healthy individuals and patients with acute concussions who had shorter recovery times (<3 weeks) demonstrated a learning effect on the KD test after mild to moderate exertion, whereas patients with longer recovery times did not. Objective To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Previous research on K-D performance after an exertion protocol validated the K-D's use in predicting recovery, but it had not been used outside the context of exertion until now. 60,61 Last and most importantly, findings from this study offer preliminary support for the utilization of norm-based healthy patient data when predicting prolonged recovery in adolescent SRC patients (89.4% accuracy). Regardless of preinjury (eg, baseline) test data availability, clinicians may be able to provide prognostic information to their patients.…”
Section: Discussionmentioning
confidence: 54%
“…Previous research on K-D performance after an exertion protocol validated the K-D's use in predicting recovery, but it had not been used outside the context of exertion until now. 60,61 Last and most importantly, findings from this study offer preliminary support for the utilization of norm-based healthy patient data when predicting prolonged recovery in adolescent SRC patients (89.4% accuracy). Regardless of preinjury (eg, baseline) test data availability, clinicians may be able to provide prognostic information to their patients.…”
Section: Discussionmentioning
confidence: 54%
“…The results of this study provide evidence on the reliability of the K-D ET, and in particular the eye-tracking components. Although previous research 19,23,35 on the number naming task (time only) has shown the K-DT to be a reliable tool under an exercise intervention, these studies did not directly measure eye tracking components. This is vital as the use of the K-DT may be increasing and the combination of the K-DT and eye tracking as one single package highlights the need to specifically measure the reliability of this combined unit.…”
Section: Discussionmentioning
confidence: 97%
“…Data was collected before and after a competitive season of 15 games over ten weeks. The researchers first obtained anthropometric data, including height and weight; followed by the K-D test performed according to manufacturer’s recommended guidelines 21 , 22 , 23 ) . The K-D test required the participants to read a series of numbers from three separate cards as fast as possible without errors.…”
Section: Participants and Methodsmentioning
confidence: 99%